Loss of STING expression is prognostic in non–small cell lung cancer. Issue 6 (31st January 2022) - Lohinai, Zoltan; Dora, David; Caldwell, Charles; Rivard, Christopher J.; Suda, Kenichi; Yu, Hui; Rivalland, Gareth; Ellison, Kim; Rozeboom, Leslie; Dziadziuszko, Rafal; Mitchell, Paul; John, Thomas; et al.
Abstract: Background: Stimulator of interferon (IFN) genes (STING) is a protein that promotes type I IFN production essential for T‐cell activation. In this study, we aim to characterize STING expression comprehensively using The Cancer Genome Atlas (TCGA) database, cell lines, and patient tumor samples stained with immunohistochemistry. Methods: Two cohorts were evaluated comprising 721 non–small cell lung cancer (NSCLC) patients and 55 NSCLC cell lines for STING and cyclic GMP‐AMP synthase (cGAS) expression using immunohistochemistry. Moreover, an independent cohort of n = 499 patients from the TCGA database was analyzed. Methylation was evaluated on STING and cGAS in five STING‐negative NSCLC cell lines. Results: STING RNA expression positively correlates with T cell function and development genes, negatively correlates with cell proliferation and associated with increased survival (5‐year‐overall survival [OS] 47.3% vs. 38.8%, p = 0.033). STING protein expression is significantly higher in adenocarcinoma (AC) and is lost with increasing stages of AC. STING‐positivity is significantly higher in mutant EGFR and KRAS tumors. STING‐positive NSCLC patients identified with immunohistochemistry (H‐score > 50) have increased survival (median OS: 58 vs. 35 months, p = 0.02). Treatment of STING‐negative cell lines with a demethylating agent restores STING expression. Conclusions: STING is ubiquitously expressed in NSCLC and associated with T cell function genes, AC histology, EGFR, and KRAS mutations and improved overall survival.